Exudate collection using wound sponges—An easy, non‐invasive and reliable method to explore protease activities in ulcers. Issue 2 (27th April 2017) - Ruf, Marie‐Thérèse; Andreoli, Arianna; Vujic, Gabriel; Itin, Peter; Pluschke, Gerd; Schmid, Peter
Abstract: Proteases are important for wound healing, but in excessive amounts or left uncontrolled, they may cause healing impairment or other severe wound complications. Point‐of‐care testing for protease activities in wounds may be useful for monitoring the effectiveness of treatment, and for early identification of wounds that potentially fail to heal. Here we describe an easy, noninvasive method to collect wound fluid for evaluating the protease milieu of wounds. Wound fluids were collected using sterile sponges applied between wound surface and normal wound dressing. Wound fluid could be easily squeezed or centrifuged out of the sponges and was tested for gelatinase (MMP‐2 and MMP‐9) activities by gel zymography. In addition, we measured polymorphonuclear granulocyte elastase levels by ELISA. Both gelatinases were remarkably stable in sponge derived fluids, as no significant loss was observed even when samples were stored for 3 days at room temperature. Protease levels were highly diverse amongst patients and, in some cases, showed substantial variations in the course of the treatment. The here described wound sponge approach represents a patient‐friendly and reliable method to collect wound fluid for evaluating wound healing relevant biomarkers, such as matrix metalloproteinases.